Analysis of Organophosphate Residues in Oranges (Citrus Sinensis L.) from Selected Markets in Lagos State, Nigeria (Nigerian Journal of Pharmaceutical Research, 2026)
Background: Pesticide residues in food pose health risks, prompting this study to determine organophosphate pesticide concentrations in oranges (Citrus sinensis) from Lagos State markets.Objective: This study aimed to determine the presence of organophosphate residues in oranges (Citrus sinensis L.) from selected markets in Lagos state, Nigeria, and to compare the detected levels with established Maximum Residue Limits (MRLs).Method: Orange samples were collected from four markets in Lagos. Residues of twenty-two organophosphate pesticides were extracted using a modified QuEChERS protocol, purified through solid-phase extraction clean-up, and analyzed via gas chromatography coupled with mass spectrometry (GC–MS).Results: The results showed that the presence of dimethoate, fenitrothion, chlorpyrifos, ethion, and malathion was detected in all samples, with mean concentrations between 0.0337 and 0.1617 mg/kg, while etrimfos, chlorfenvifos, triazophos, and azinfos-methyl were detected in some samples at concentrations between 0.0065 and 0.0753 mg/kg.Conclusion: Oranges from Lagos State markets contain organophosphate pesticide residues within limits, below the maximum residue levels (MRLs) established by regulatory agencies. Continuous monitoring is necessary to ensure consumer safety and maintain acceptable residue levels, preventing potential health risks associated with pesticide exposure.